Metabolic syndrome in healthy obese, overweight, and normal weight individuals: The atherosclerosis risk in communities study - Bradshaw, Patrick T.; Monda, Keri L.; Stevens, June (Obesity (Silver Spring, Md.), 2013)
Objective: There is recent interest in characterizing the subset of obese (OB) individuals who have healthy metabolic profiles yet only two studies have examined this group prospectively but not in racially diverse populations. Design and Methods: We analyzed factors associated with the prevalence and incidence of metabolic syndrome (MetSyn) among individuals grouped by BMI categories in a multi‐center, community‐based cohort of 14,663 African‐American and white men and women aged 45‐64 years at recruitment in 1987‐1989, the Atherosclerosis Risk in Communities (ARIC) Study. Logistic and proportional hazards regression were utilized to estimate odds ratios (ORs) for the prevalence and hazard ratios (HRs) for incidence of MetSyn with 95% confidence intervals (CIs). Results: At visit 1, MetSyn was positively associated with age, female gender, African‐American race, and inversely related to education, associations being more pronounced among normal weight (NW) subjects. Among those without MetSyn at visit 1, OB subjects were more likely to develop MetSyn compared with NW (HR (95% CI): 4.53 (4.09‐5.01)). Several factors were associated with incident MetSyn among NW, including older age (per year: 1.05 (1.03‐1.06)), female gender (vs. male: 1.29 (1.10‐1.52)), heavy alcohol intake (vs. never: 0.75 (0.59‐0.94)), and physical activity (tertile 3 vs. tertile 1: 0.71 (0.58‐0.86)) but not OB. Weight gain (>5%) was also more highly associated with MetSyn in NW (1.61 (1.28‐2.02)) compared with OB (1.01 (0.85‐1.20)). Conclusions: We conclude that lifestyle factors may play a stronger role in the development of MetSyn in NW individuals compared with OB and that metabolically healthy obesity may not be a stable condition.